Pengaruh Pemberian Kompos Kirinyuh (Chromolaena odorata L.) terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Syafitri, Novi; Rezki, Dewi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2022)
Cacao is one of the primary plantation commodities that plays an important role in the Indonesian economy. The objectives of this research were to study the effects of siam weed compost on the growth of cacao seedlings and to determine the best dose of siam weed compost on the growth of cacao seedlings. This research was conducted at the experimental field 3rd Campus, Andalas University in Dharmasraya. The research method was a Completely Randomized Design (CRD) by 5 treatments of siam weed compost, there were = 0 g/polybag, 500 g/polybag, 750 g/polybag, 1000 g/polybag, and 1250 g/polybag. The observation data were analyzed F-test at 5 % level, if significantly different continued by the Duncan’s New Multiple Range Test (DNMRT) at 5 % level significantly. The result showed that the application of siam weed compost affected the growth of cacao seedlings, particularly increase the plant height, number of leaves, shoot dry weight, root dry weight, root fresh weight, and the length of the roots. The best dose of siam weed (Chromoaena odorata L.) compost on the growth of cacao seedlings was at a dose of 1250 g/polybag.